Enough!: A Modest Political Ecology for an Uncertain Future - Mary Lawhon; Tyler McCreary (Agenda Publishing Limited, 2023)
Enough! insists there is enough for all. Creating such a future is not about producing more or living with less. Instead, it starts with rethinking our politics, economics and approach to livelihoods. Mary Lawhon and Tyler McCreary develop a "modest approach" to justice and sustainability, drawing on ecology and postcolonial theory, as well as their research on infrastructure in African cities and the Canadian north. The authors chart a pathway beyond modernist and arcadian environmentalisms, emphasizing uncertainty while holding onto hope for creating better worlds. The chapters tack between conceptual contours, concrete examples, proposed inventions, and personal narrative. Theorizing from the struggles of the global south and Indigenous peoples, Enough! proposes delinking livelihoods from work through a redistributive basic income, which enables enough without overreliance on modern states. It also enables us to prevent conflicts over jobs, reduce some types of production, and deploy resources towards building postcapitalist worlds.
Keywords: 320; political ecology; universal basic income; communitiy economies; emplaced sustainability